2020
DOI: 10.3389/fpsyt.2020.00587
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Impairment of Mismatch Negativity Is Reflective of Underlying Pathophysiological Changes in Patients With First-Episode Psychosis

Abstract: Background: Although mismatch negativity (MMN) is associated with the pathophysiology of schizophrenia, whether MMN progressively worsens during the initial years of psychotic disorder has not yet been sufficiently studied. We aimed to investigate whether longitudinal reduction of MMN occurs in patients with first-episode psychosis (FEP) and whether it is reflective of change in cognitive functioning or clinical status. Methods: MMN and the clinical status of 25 patients with FEP were measured and the Trail Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Most of the studies did not find significant differences between HCs, FEP ( 188 , 189 ), FES ( 193 , 194 , 198 , 201 , 206 ), and HR subjects ( 180 , 194 , 201 , 204 , 206 , 207 ) in dMMN latency, with the exception of one study that found delayed latency in dMMN peak in FEP subjects ( 196 ), as compared to HCs.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Most of the studies did not find significant differences between HCs, FEP ( 188 , 189 ), FES ( 193 , 194 , 198 , 201 , 206 ), and HR subjects ( 180 , 194 , 201 , 204 , 206 , 207 ) in dMMN latency, with the exception of one study that found delayed latency in dMMN peak in FEP subjects ( 196 ), as compared to HCs.…”
Section: Resultsmentioning
confidence: 91%
“…Discrepant findings have been reported with the regard to the dMMN amplitude. In particular, some studies found a reduction of dMMN amplitude in FEP (66,151,(188)(189)(190)(191) and FES subjects (65,95,181,182,190,(192)(193)(194)(195)(196) as compared to HCs, while other studies did not find any abnormality in dMMN amplitude in FEP and FES subjects (183,(197)(198)(199)(200). Furthermore, a study, involving ML to distinguish FES from HCs with dMMN measures in addition to other neuroimaging and clinical evaluations, highlighted that this EEG-index did not contribute significantly to the discriminant ML-model (158).…”
Section: Dmmnmentioning
confidence: 99%
“…While dMMN may be a more static biomarker of schizophrenia than fMMN, our earlier study in CHR cohort suggested that dMMN amplitude may also exhibit longitudinal decline during transition period into psychosis ( 29 ). The study by Lho et al also showed a decrease in dMMN of FES over time ( 23 ). Thus, future longitudinal studies in a larger cohort at various stages of psychosis would be required to clarify the specific role of MMN in the disease pathophysiology ideally using a multimodal approach (e.g., neuroimaging and biochemical investigations).…”
Section: Discussionmentioning
confidence: 93%
“…However, previous studies have suggested the role of MMN as a "breakthrough biomarker" for schizophrenia (19); it has reduced amplitude with larger effect size than other psychiatric disorders such as bipolar disorder (20), remains stable over time, and is independent of staterelated changes (21). In particular, reduced amplitude of dMMN exists in various stages of psychosis, including CHR status before onset and both first-episode and chronic stages of schizophrenia (22)(23)(24), as a rather stable vulnerability marker and also reflects cognitive and social functions in various clinical conditions (25,26). It has been demonstrated that high baseline amplitude of dMMN in CHR individuals is associated with functional and symptomatic improvement regardless of psychosis onset (27,28), potentially implicating its role as a predictor of remission in patients with psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation